Women's skills and aptitudes as drivers of organizational resilience: An Italian case study - Antonietta Cosentino; Paola Paoloni (Administrative Sciences, 2021)
The economic system has experienced heavy consequences caused by the recent pandemic. This paper investigates the interaction between the crisis and organization reaction, focusing on the female managerial role and contribution to overcoming the crisis in male-owned and managed companies. To achieve the research objectives, we used a qualitative research method based on an explorative case study. The results show that female managerial skills have fostered organizational resilience in terms of: (i) the attitude to change; (ii) the ability to promote new initiatives; and (iii) the ability to have initiated, consolidated, and managed solid formal relationships with institutional stakeholders. Our results also highlight the decisive contribution of corporate governance (even if male-oriented) in favoring the growth and autonomy of women in positions of responsibility. This contribution is evidenced by (iv) increasing delegation of roles and responsibilities in managing relationships with institutional stakeholders to women managers; and (v) recognizing women managers' talents in terms of career progression. The originality of this work is represented by the survey that aims to determine how the female management of businesses managed and owned by men can foster the resilience of companies. On the other hand, this paper investigates how female leadership drives organizational resilience during unexpected shocks, opening an interdisciplinary viewpoint.
Keywords: 350; COVID-19; personal aptitude; relational capital; skills; woman managers